Experimental and numerical studies on the heating mechanism of millimeter multi-particle system under microwave irradiation. (June 2022) - Li, Junfeng; Zhou, Wei; Su, Yanlin; Wei, Siyu; Zhao, Yang; Zhang, Lei; Ding, Yani; Xie, Liang; Sun, Fei; Gao, Jihui; Wang, Pengxiang; Zhao, Guangbo; et al.
Abstract: Microwave heating has been widely used in multi-particle system due to its high heating rate and low energy consumption. However, the mechanism of hot spots evolution during microwave heating of millimeter multi-particle system is still not clear. In this study, the phenomenon of the formation and development of multiple hot spots has been observed in the microwave heating experiment and numerical simulation. Besides, the transform of the resonance mode in the container was observed and analyzed by numerical simulation, which means the heating properties of the particles are affected by the combination of dielectric characteristics and particle size. For millimeter particles, the resonance mode of microwave absorption converts from the bonding mode to the mixed-mode (bonding mode + central mode) with the increase of εr '. Additionally, for millimeter carbonous particles, the resonance mode change occurs roughly at εr ' = 14, and the effect of particle size on microwave absorption is mainly reflected in energy efficiency. Altogether, this work promotes the understanding of microwave heating of multi-particle systems and provides references for the efficient heating of different materials. Graphical abstract: Image 1 Highlights: The multiple hot spots was discovered during microwave heating of multi-particles. The resonant mode of particles converts with the change of dielectric properties. For millimeter carbonous particles, the resonance mode change occurs at εr ' = 14. Microwave absorption is affected by both particle size and dielectric properties.